Interdependence of neck pain prevalence with neck disability and sleep quality among Nigerian seamstresses - Jehurat Abdulahi; Adebisi Hammed; Nicholas Oghumu; David Akintayo; Solomon Ogbouma; Martins Okhawere; Imuwahen Mbarie; Ayobami Fasuba; Kayode Oke (Exercise and Quality of Life)
Seamstresses, due to the nature of their profession, often face ergonomic challenges stemming from prolonged sitting, repetitive motions, and the adoption of awkward postures. These factors could affect sleep quality and contribute to an increased risk of musculoskeletal disorders, including but not limited to, carpal tunnel syndrome, neck and back pain, and shoulder strain. It seems necessary, therefore, to evaluate the association of neck pain prevalence with neck disability and sleep quality among Nigerian seamstresses. 169 participants of ages 18 and above with varying levels of experience were recruited using a convenience sampling technique. The measure employed has 4 sections containing socio-demographics, Nordic Musculoskeletal Questionnaire, the Sleep Quality aspect of the Pittsburgh sleep quality index and Neck Disability Index. Descriptive statistics such as frequencies, and percentages were used to summarize the data and provide an overview of the respondents’ prevalence of neck pain. Pearson’s Chi square was used to test the association of neck pain prevalence with sleep quality and neck disability at 0.05 alpha level. The lifetime and 12-month prevalence of neck pain were 83.4% and 73.4% respectively. 39 (23.1%) reported good sleep quality. About 45.6% of the respondents’ reported no neck disability. There is no statistically significant relationship between neck disability and the prevalence of neck pain (X2 = 6.416, p = 0.601). However, a significant relationship was observed between the prevalence of neck pain and sleep quality (X2= 4.411, p = 0.036). Seamstresses have a high prevalence of neck pain due to long hours of static positions. Poor sleep quality was also associated with neck pain. Nonetheless, there was no significant relationship between neck disability and pain prevalence, although, sleep quality, pain intensity, and neck disability are interconnected in the present study.